Bank deregulation and monetary order - Selgin, George A., 1957- (Routledge international studies in money and banking, 1996)
Can the 'invisible hand' manage money? George Selgin challenges the view that government regulation creates monetary order and stability, and instead shows it to be the main source of monetary crisis.